EVALUASI STRATEGI BERSAING SMA KRISTEN 1 SALATIGA - Eclesia Tehupeiory; Bambang Suteng Sulasmono (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aims to evaluate the competitive strategies of SMA Kristen 1 Salatiga. The type of this study was a qualitative evaluation, through data collection by means of interviews, questionnaires, observation and documentation study. Data obtained and analyzed by an evaluation component based on Rumelt (2000) were consistency, consonance, advantage and feasibility. The results showed that: (1) Consistency evaluation of competitive strategy applied by SMA Kristen 1 Salatiga has shown consistency with the goals, values and policies of the school. (2) Consonance evaluation of competitive strategy has demonstrated suitability with the needs of society, while for competition with other schools, the school programs such as Peduli Kasih program, Sekolah Lima Hari, moving class, SMUQI Radio and multimedia extracurricular namely cinematography and photography are not appropriate. (3) Advantage evaluation of competitive strategy in the school programs such as Peduli Kasih, moving class, and Sekolah Lima Hari do not excel the resources, skills and superior positions. Other programs such as multimedia Extracurricular namely photography and cinematography is not superior to the superior position. Meanwhile, special programs such as the education expo, parenting day, career day and the Field Trip program through Live In and outdoor study do not excel in superior skills. (4) Feasibility evaluation shows that multimedia extracurricular programs have not showed the feasibility of the physical resources which involves computer supporting facilities and Wi-Fi. Suggestion to school in order to maintain the consistency that was owned, suitability to the needs of society as well as pay attention to competition with other schools also enhance the achievement of advantage and checking of IT facilities.